PERAN ORANG TUA TERHADAP MINAT BACA ANAK USIA 7 TAHUN, DI NAGARI BALAH AIE UTARA, KECAMATAN VII KOTO SUNGAI SARIK - Permata, Okma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to determaine the role of parents in invreasing children’s interest in reading and its influence factors by using qualitative descriptive methods. The processing and collection of data is carried out through observation, interviews and notes. The subjects in this research were parents and children’s interest in reading. The location of this research is Nagari Balag Aie Utara, Kecamatan VII Koto sungai Sarik. The results of this research show that parents are the first education for their children, however currently there are still parents who do not pay attention to their children’s learning development, especially their children’s interest in reading. The role of parents is very necessary, so that children are motivated and feel cared for. As a result, children are enthusiastic in learning to read.Keywords: The role of parents, interest in reading, children.